Mungkinkah Koruptor Dihukum Mati? Analisis Perdebatan tentang Pelaksanaan Hukuman Mati di Indonesia - Khaeron Sirin (UIN Sunan Kalijaga Yogyakarta, 2015)
Crimeof corruptioninIndonesiahas causedenormousdestructionto the survival ofthe state and nation.Notonlydetrimental tothe state,but italso snatchedsocial rightsand economic developmentin general. This crimeis verydifficult to eradicate, becauseitis oftendonein a systematicand involvethe peoplein power. Wecan feelhow greatand extraordinarydangerscaused bythis crime. It istrueif thiscrimeisclassified asan extraordinary crimethat must be eradicatedbya remarkable wayas well, that is by way of executingthe perpetratorsof corruptionin this country.